Protamine sulfate use during tibial bypass does not appear to increase thrombotic events or affect short-term graft patency. (December 2020) - Phair, John; Futchko, John; Trestman, Eric B; Carnevale, Matthew; Friedmann, Patricia; Shukla, Harshal; Garg, Karan; Koleilat, Issam
Objectives: While the use of protamine sulfate as a heparin reversal agent has been extensively reviewed in patients undergoing carotid endarterectomy and coronary artery bypass grafting, there is a lack of literature on protamine's effects on lower extremity bypasses. The purpose of this study was to determine the risk of protamine sulfate dosing after tibial bypass on thrombotic or bleeding events, including early bypass failure. Methods: We performed a retrospective review of our institutional database for patients undergoing primary distal peripheral bypass from January 2009 through December 2015 (contralateral bypass was considered to be a new primary bypass). Primary endpoints include composite thrombotic events (myocardial infarction, stroke, amputation at 30 days and patency less than 30 days) and composite bleeding events (bleeding or transfusion). Results: A total of 152 tibial or peroneal bypasses in 136 patients with critical limb ischemia were identified. Of these, 78 (57.4%) patients received protamine sulfate intraoperatively and 58 (42.6%) did not. There were no differences in composite thrombotic or hemorrhagic outcomes. Protamine use had no effect on the rates of perioperative MI (9.0% versus 3.5%, p = 0.20), stroke (1.3% versus 1.7%, p = 0.83), or perioperative mortality (5.1% versus 3.5%, p = 0.64). There was no significant difference in composite post-operative bleeding events (20.7% versus 14.1%, p = 0.31) or composite thrombotic events (17.2% versus 18.0%, p = 0.91). Patients who received protamine undergoing bypass with non-autogenous conduit had significantly higher-recorded median operative blood loss (250 mL versus 150 mL, p = 0.0097) and median procedure lengths (265 min versus 201 min, p = 0.0229). No difference in 30-day amputation-free survival was noted (91.0% versus 91.4%, p = 0.94). Follow-up Kaplan–Meier estimation did not demonstrate a difference in 30-day patency (91.7% versus 88.5%, p = 0.52). Conclusions: Heparin reversal with protamine sulfate after tibial or peroneal bypass grafting is not associated with higher cardiovascular morbidity, bypass thrombosis, amputation, or mortality. Additionally, there was no statistically significant difference in post-operative bleeding or thrombosis complications for patients who did not receive protamine, although the findings are suggestive of a potential difference in a more adequately powered study. Our results suggest that protamine sulfate is safe for intraoperative use without increased risk of thrombotic complications or early tibial bypass graft failure.